Serum cystatin C was a marker of poststroke fatigue in hypertensive intracerebral hemorrhage. Issue 2 (26th November 2020) - Yang, Fulan; Liu, Peipei; Huang, Saiyu; Liu, Xiaojie; Gao, Xue; Liu, Chunyin; Chen, Lanlan; Chen, Yingzhu
Abstract: Introduction: The relationship between poststroke fatigue (PSF) and serum Cystatin C (Cys‐C) levels in hypertensive intracerebral hemorrhage (HICH) patients has not been determined. In this study, we investigated the association between serum Cys‐C levels and PSF in HICH patients. Methods: A total of 125 patients with HICH were enrolled. Fatigue assessment was performed 6 months after HICH onset. The presence of PSF was defined as Fatigue Severity Scale (FSS) of 4 or more. Serum Cys‐C levels were measured within 24 hr after admission. The correlation between FSS score and Cys‐C level was analyzed by Spearman's correlation. Receiver operating characteristic (ROC) curves for PSF were calculated using Cys‐C values. Results: Of enrolled 125 patients in the study, 36.0% who developed PSF were divided to the PSF group, which had higher Cys‐C levels compared with the no‐PSF group. There was significant positive correlation between FSS score and serum Cys‐C level. Receiver operating characteristic curves for PSF revealed an area under the curve of 0.86 for Cys‐C. High admission Cys‐C (>0.75mg/L) yielded specificity of 93.7%, positive predictive value of 87.5%, and negative predictive value of 88.2%. In multivariate analysis, Cys‐C increased by 1 mg/dl (0.1 mg/L), and the risk of PSF in patients increased by 2.55 times (odds ratio = 2.55, 95% CI: 1.65–3.95, p < .001). Conclusions: High Cys‐C levels have predictive value for PSF and can be used as one screening indicator for PSF occurrence. Abstract : High Cys‐C levels have predictive value for PSF and can be used as one screening indicator for PSF occurrence. High admission Cys‐C (>0.75 mg/L) yielded specificity of 93.7%, positive predictive value of 87.5%, and negative predictive value of 88.2%.